Answer:
amdlkmflakmflkmasdklmflkansdlkfwelkma;lkdsmlfdsnalkme;klamdlfsndldkanfdlknadlkfn;alkndflkandslknaslfknalkdfnladkfsnlkandslfkn
Step-by-step explanation:
The factored expression of m(2a+b)-n(2a+b)+2n(2a+b) is (m + n)(2a + b)
<h3>How to factor the expression?</h3>
The expression is given as:
m(2a+b)-n(2a+b)+2n(2a+b)
Factor out 2a + b
m(2a+b)-n(2a+b)+2n(2a+b) = (m - n + 2n)(2a + b)
Evaluate the like terms
m(2a+b)-n(2a+b)+2n(2a+b) = (m + n)(2a + b)
Hence, the factored expression of m(2a+b)-n(2a+b)+2n(2a+b) is (m + n)(2a + b)
Read more about factored expressions at:
brainly.com/question/723406
#SPJ1
Answer:
I(x)=x+1
Step-by-step explanation:
Answer:
1.) A' = (4,-4)
B' = (2,-4)
C' = (2,-2)
D' = (4,-2)
2.) A' = (-1,5)
B' = (-2,1)
C' = (0,1)
Hope this helps!
And please mark as brainliest!